Pengaruh Iklan Televisi terhadap Perilaku Pembelian Anak-Anak Di Kabupaten Pati - Imami Mashuri, Dian; Yoki Febrima, Achmad; Wulan Intan Palupi, Nur (MEDIA RISET EKONOMI [MR.EKO], 2024)
This research examines the influence of television advertising on children's purchasing decisions in Pati Regency. The population studied in this research were children living in Pati Regency aged 13 to 17 years who watched television advertisements. Of the 225 respondents in the research sample, 202 responses, or 89.78%, were accepted and suitable for analysis. Data was collected through questionnaires. Samples were taken using convenience and purposive sampling methods. Data analysis was carried out with IBM Statistical Program for Social Sciences (SPSS) using multiple linear regression. The research results show that quality information, information intrusiveness, and preferred advertising have a positive and significant effect on children's purchasing behavior. This research suggests that the information presented is quality, accurate, reliable and timely about products and the use of popular and well-liked artists in television advertising.